Inovasi Rasa dan Strategi Pemasaran: Kunci Sukses UMKM Seblak di Tengah Persaingan - Dhermawan, Faisal; Sari, Putri Delvina; Fauziah, Yupita Asmul; Dalilla, Dea; Priyandini, Marliana; R, Rismawati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze flavor innovation and marketing strategies as the main factors in the success of Micro, Small, and Medium Enterprises (MSMEs) seblak in Indonesia. Seblak, as a typical food that is increasingly popular, has experienced fierce competition along with increasing market demand. To survive and thrive, MSME seblak actors are required to innovate, both in terms of flavor variations and marketing methods. This study identifies the types of flavor innovations that are most in demand by consumers and analyzes effective marketing strategies, such as the use of social media, digital promotions, and collaboration with influencers. The results of the study show that unique flavor innovations and the implementation of appropriate digital marketing strategies can increase the competitiveness of MSME seblak, attract new consumers, and expand market share. In conclusion, the combination of flavor innovation and adaptive marketing strategies is the key to maintaining existence and achieving success in a competitive market and sustainable HR management to address the evolving business dynamics.